Comparison of speed endurance between rural and urban adolescent soccer players - Akeepan, S.; Sabaananth, S. (Sri Ramakrishna Mission Vidyalaya, 2017)
Speed endurance is an important factor to determine tempo of the game/ sport. In soccer the player who can immediately establish speed with low recovery may succeed the game demand. The aim of the study was to compare Speed Endurance between rural and urban adolescent boys. To achieve the purpose of the study forty footballers (15-17 years) purposively selected from Jaffna, Sri Lanka. The selected subjects were divided in two group of twenty each. Group I (urban, n=20, practice football 120 min/day/3days/week/ over the period of minimum 7 years) and Group II (n= rural 20, practice football 120 min/day/3days/week/ over the period of minimum 7 years). The Data were collected on speed endurance by using sprint fatigue test and collected data were statistically analyzed by using independent- samples ‘T’ test. The results revealed that urban footballers are better than rural footballers on speed endurance. Hence it was concluded that, urban footballers were better than rural footballers, due to the good nutrition, knowledge of the coach and the way to familiarize to advance science training. From the result of this study it was recommended that, science base training and good nutrition leads to good training adaptation. Thus enrich the tempo and beauty of the soccer match.
Keywords: Speed endurance; fatigue; sprint